Safe and Efficient Preparative Approach to Chiral α-Chloroketones Based on In-Flow Generated Diazomethane - Viacheslav V. Pendiukh; Alexander B. Rozhenko (Журнал органічної та фармацевтичної хімії)
α-Chloroketones are valuable semi-products in the organic synthesis and pharmaceutical industry. In particular, they are used as key building blocks for the production of HIV protease inhibitors, such as atazanavir and darunavir. A well-known approach to their synthesis involves the Arndt-Eistert homologation, which relies on the formation of diazoketones followed by their halogenation. However, this process poses significant safety and implementation challenges due to the use of diazomethane (CH2N2). The high toxicity, carcinogenicity, and explosion hazard of CH2N2 limit its large-scale application and require design of specialized laboratory setups to reduce the risks.